Response to Student Literacy Needs at Mother of Sorrows Catholic School - Beltramo, Jennifer A. (Catholic Education: A Journal of Inquiry and Practice, 2012)
More than ever, the challenges facing Catholic schools and Catholic school leaders require a “readiness to renew and adapt” (Vatican Council II, 1965). The skills and dispositions developed through applied action research—inquiry that is systematic, practitioner-driven, and change oriented—are integral to the formation of teachers and leaders who will meet these challenges head on and strengthen Catholic schools for generations to come. The following action research project was conducted by a Catholic school leader who is a recent graduate of the Mary Ann Remick Leadership Program at the University of Notre Dame. The article you will read is one product of the comprehensive, four-course action research sequence that is a hallmark of the Remick Leadership Program, and is discussed in greater detail in the focus section overview. As you read on, you will notice that action research is highly contextualized—responsive to the specific needs in a particular school community—but also reflective of the broader educational research literature, and the rich traditions and teachings of our Catholic faith. We hope this action research inquiry informs your own practice, and inspires you to pursue mission driven and data informed leadership practices to bring about positive change in your own school or community. Nearly 90% of intermediate and middle school students from low-income families in the United States are not proficient in reading. This action research project used a quasi-experimental design to determine the effectiveness of a multi-component reading intervention program for students in grades four through eight at Mother of Sorrows Catholic School in Los Angeles, California. The study analyzed standardized measures for fluency, word study, and reading comprehension. It also examined the program’s influence on student perceptions of reading. Data analysis indicated that all five grades achieved a statistically significant increase between pretest and posttest scores for all three areas of reading. In addition, students were able to make comparable gains regardless of their initial performance above or below grade level.